Anaplasma, Ehrlichia and Rickettsia species infections in cats: European guidelines from the ABCD on prevention and management. Issue 5 (May 2017) - Pennisi, Maria Grazia; Hofmann-Lehmann, Regina; Radford, Alan D; Tasker, Séverine; Belák, Sándor; Addie, Diane D; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hartmann, Katrin; Horzinek, Marian C; et al.
Overview: Anaplasma species, Ehrlichia species and Rickettsia species are vector-borne pathogens infecting a wide variety of mammals, but causing disease in very few of them. Infection in cats: Anaplasma phagocytophilum is the most important feline pathogen among these rickettsial organisms, and coinfections are possible. Little information is available on the pathogenesis of these agents in cats. Clinical signs are usually reported soon after tick infestation. They are mostly non-specific, consisting of fever, anorexia and lethargy. Joint pain may occur. Infection in humans: Some rickettsial species ( A phagocytophilum, Ehrlichia chaffeensis, Ehrlichia ewingii, Rickettsia conorii, Rickettsia rickettsii, Rickettsia felis, Rickettsia typhi and Candidatus Neoehrlichia mikurensis) are of zoonotic concern. Direct contact with cat saliva should be avoided because of potential contamination by R felis . Infected cats are 'sentinels' of the presence of rickettsial pathogens in ticks and fleas in a given geographical area, and they signal a risk for people exposed to vectors.